ELECTRODYNAMIC FEATURES OF METAL MIXING - Levchenko, Serhii; Kovalenko, Victor; Artemchuk, Victor; Bashliy, Serhii; Yerofieieva, Alina (Scientific Journal "Metallurgy", 2022)
The method of theoretical research is proposed with the help of conformal reflections on determination of forces on metal melting in electro-steel furnaces taking into account the purposeful action of the magnetic field. The type of magnetic field with two-phase stator is analyzed. Based on the proposed method of using conformal display, it is possible to determine the traction force at each melt point. Proposed functions of conformal reflections, the use of which allows you to switch from non-dimensional magnetic field to a set of mutually perpendicular lines. The functions of transition from uneven magnetic field to uniform field are proposed. It is noted that the difficulty in the selection of conversion functions and the application of the Kristoffel-Schwartz integral. Replacement of integral equations to determine the overall force that creates the movement of metal melt, to algebraic functions of conformal reflections makes it possible to develop appropriate computer programs for automatic regulation of power of induction-arc steel furnaces, which are the basis for the design of modern electrometallurgical complexes with improved technical and economic indicators that are able to ensure the competitiveness of domestic metallurgical production.